Lipid profile in Noonan syndrome and related disorders: trend by age, sex and genotype - Tamburrino, Federica; Mazzanti, Laura; Scarano, Emanuela; Gibertoni, Dino; Sirolli, Maria; Zioutas, Maximiliano; Schiavariello, Concetta; Perri, Annamaria; Mantovani, Alessio; Rossi, Cesare; Tartaglia, Marco; Pession, Andrea (Frontiers in Endocrinology, 2023)
Background RASopathies are developmental disorders caused by dysregulation of the RAS-MAPK signalling pathway, which contributes to the modulation of multiple extracellular signals, including hormones and growth factors regulating energetic metabolism, including lipid synthesis, storage, and degradation. Subjects and methods We evaluated the body composition and lipid profiles of a single-centre cohort of 93 patients with a molecularly confirmed diagnosis of RASopathy by assessing height, BMI, and total cholesterol, HDL, triglycerides, apolipoprotein, fasting glucose, and insulin levels, in the context of a cross sectional and longitudinal study. We specifically investigated and compared anthropometric and haematochemistry data between the Noonan syndrome (NS) and Mazzanti syndrome (NS/LAH) groups. Results At the first evaluation (9.5 + 6.2 years), reduced growth (-1.80 ± 1.07 DS) was associated with a slightly reduced BMI (-0.34 DS ± 1.15 DS). Lipid profiling documented low total cholesterol levels (< 5th percentile) in 42.2% of the NS group; in particular, in 48.9% of PTPN11 patients and in 28.6% of NS/LAH patients compared to the general population, with a significant difference between males and females. A high proportion of patients had HDL levels lower than the 26th percentile, when compared to the age- and sex-matched general population. Triglycerides showed an increasing trend with age only in NS females. Genotype-phenotype correlations were also evident, with particularly reduced total cholesterol in about 50% of patients with PTPN11 mutations with LDL-C and HDL-C tending to decrease during puberty. Similarly, apolipoprotein A1 and apolipoprotein B deficits were documented, with differences in prevalence associated with the genotype for apolipoprotein A1. Fasting glucose levels and HOMA-IR were within the normal range. Conclusions The present findings document an unfavourable lipid profile in subjects with NS, in particular PTPN11 mutated patients, and NS/LAH. Further studies are required to delineate the dysregulation of lipid metabolism in RASopathies more systematically and confirm the occurrence of previously unappreciated genotype-phenotype correlations involving the metabolic profile of these disorders.